고주파 통증치료기를 이용한 재활 치료에 대한 연구 - 조재현(Jae-Hyun Jo); 이상용(Sang-Yong Lee); 이근용(Geun-Yong Lee); 윤세진(Se-Jin Yoon); 정하영(Ha-Young Cheong); 이상식(Sang-Sik Lee) (한국정보전자통신기술학회 논문지, 2020)
When Radiofrequency energy is applied to the human body, the vibration width is very short. Therefore, the electrolyte burn generated when using the direct current does not occur. Ion molecules, polarized molecules, etc., vibrate more than 40,000 times per second, converting them into frictional heat to generate deep heat. The blood flow of capillaries increases 4-5 times more than at rest, increasing the supply of oxygen, nutrients, antibodies, and white blood cells. In addition, the electrochemical reaction does not occur because the vibration width and the pulsation period are very short. It is a physical factor treatment method that does not stimulate the sensory nerves and motor nerves. In this study, an isotonic exercise is performed in a young normal adult using a Radiofrequency pain treatment device. The purpose of this study is to integrate rehabilitation therapy by measuring electromyography data during isotonic exercise and confirming the effect on changes in motor neuron response. The EMG data generated when isotonic exercise of the forearm biceps muscle and the EMG data measured after the use of a Radiofrequency pain treatment device after exercise were RMS, respectively, and verified through t-test. It was confirmed that there was a significant difference in both men and women because the t-value was smaller than the significance level p (<.05). 인체에 고주파 에너지를 가하면 진동 폭이 매우 짧아서 직류 전류 이용 시 발생하는 전해질 화상이 일어나지 않으며 이온분자, 분극분자 등이 초당 4만 번 이상 진동을 하면서 마찰열로 전환되어 심부열을 발생시켜 모세혈관의 혈류량은 휴식 시 보다 4~5배 증가하여 산소, 영양물질, 항체, 백혈구 등 공급의 증가한다. 또한 진동 폭과 맥동기간이 매우 짧아 전기 화학적 반응이 일어나지 않으며 감각신경과 운동신경을 자극하지 않는 물리적 인자치료 방법이다. 본 연구에서는 고주파통증치료기를 사용하여 젊은 정상 성인을 대상으로 등장성운동을 시키고, 등장성 운동 시 근전도 데이터를 측정하여 운동신경 응답의 변화에 미치는 영향을 확인하여 재활치료 접목시키고자 하였다. 윗팔두갈래근의 등장성 운동을 실시할 때 발생되는 근전도 데이터와 운동 후 고주파통증치료기사용 후 측정된 근전도 데이터를 각각 RMS하여 t-검정을 통하여 검증을 실시하였으며, 남녀 모두 t값, p값이 유의수준(<.05) 보다 작게 나와 유의한 차이가 있다는 것을 확인하였다.